PELAKSAAN PENGAWASAN MELEKAT DI BIRO BINA SOSIAL SEKRETARIAT DAERAH PROVINSI SUMATRA BARAT - Reza Mindasari (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about Implementation of Inherent Supervision by Leade (chief) to employee’s tasks that reviewed from supervised aspect, inherent supervisi process, supervision techniques, and supervision time (duration). The population is 65 employee and the sample is 56 people that taken by simple random sampling research. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research is implementation of inhherent (chief) to Sosial Sekretariat Daerah Provinsi Sumatra Barat. Key word : Implementation of Inherent Supervision